Burndown of Ryegrass Cover Crops Prior to Crop Planting - Jason A. Ferrell; David L. Wright; Barry J. Brecke; Gregory E. MacDonald (EDIS)
SS-AGR-269, a 3-page illustrated fact sheet by J.A. Ferrell, D.L. Wright, B.J. Brecke, and G.E. MacDonald, provides recommendations for using glyphosate to burn down ryegrass before planting, with specific information for corn, cotton, and peanuts and a table with conversion of rates based on formulation. Published by the UF Department of Agronomy, April 2007.